The GST domain of GDAP1 is a frequent target of mutations in the dominant form of axonal Charcot Marie Tooth type 2K. Issue 10 (3rd August 2010) - Crimella, C; Tonelli, A; Airoldi, G; Baschirotto, C; D'Angelo, M G; Bonato, S; Losito, L; Trabacca, A; Bresolin, N; Bassi, M T
Abstract : Background: Mutations in GDAP1 associate with demyelinating (CMT4A) and axonal (CMT2K) forms of CMT. While CMT4A shows recessive inheritance, CMT2K can present with either recessive (AR-CMT2K) or dominant segregation pattern (AD-CMT2K), the latter being characterised by milder phenotypes and later onset. The majority of the GDAP1 mutations are associated with CMT4A and AR-CMT2K, with only four heterozygous mutations identified in AD-CMT2K. Methods: We screened GDAP1 gene in a series of 43 index patients, 39 with CMT2 and 4 with intermediate CMT, with sporadic and familial occurrence of the disease. Results: Three novel mutations were identified in three families with dominant segregation of the disease: two missense changes, p.Arg226Ser and p.Ser34Cys, affecting the GST domain of the GDAP1 protein and a novel deletion (c.23delAG) leading to early truncation of the protein upstream the GST domain. Wide variability in clinical presentation is shared by all three families mostly in terms of age at onset and disease severity. A rare variant p.Gly269Arg, located within the GST domain, apparently acts as phenotype modulator in the family carrying the deletion. Conclusion: The results obtained reveal a GDAP1 mutation frequency of 27% in the dominant families analysed, a figure still unreported for this gene, thus suggesting that GDAP1 involvement in dominant CMT2 might be higher than expected.